STUDI KASUS IMPLEMENTASI AROMATERAPI LEMON PADA NY.M DENGAN EMESIS GRAVIDARUM TRIMESTER I DI PUSKESMAS KALIMANAH PURBALINGGA - Dewi, Kharisma Lala; Haniyah, Siti (STIKES Suaka Insan, 2023)
Complaints of nausea in first-trimester pregnant women can be prevented with non-pharmacological measures, including lemon aromatherapy. This study aimed to develop nursing care to help nausea patients with Emesis Gravidarum problems at the Kalimanah Health Center, Purbalingga. This type of research was a case study. The results of case studies obtained in patients after using lemon aroma therapy for three days showed decreased signs and symptoms of nausea. This case study shows that lemon aromatherapy can help reduce nausea in first-trimester gravidarum patients. Keywords: lemon aromatherapy, nausea, first.trimester gravidarum